Branchial Cleft Anomalies: Embryogenesis, Clinical Features, Diagnosis, and Management. Issue 1 (March 2022) - Prescher, Hannes; Nathan, Shelby L.; Bauer, Bruce S.; Reid, Russell R.
Branchial cleft anomalies are congenital head and neck lesions that arise from incomplete maturation of the branchial apparatus during fetal development. The branchial arches are the precursors of the face, neck and pharynx, and disturbances in embryogenesis can present clinically as cysts, sinus tracts, and fistulas in predictable anatomic locations. However, there remains controversy regarding the precise embryogenesis of branchial cleft anomalies with several competing theories. These lesions often evade diagnosis in early childhood and may present in a delayed fashion after multiple failed interventions. Various diagnostic modalities have been described to facilitate clinical workup. Definitive treatment is complete surgical excision of the lesion. We present a comprehensive review of the literature along with several illustrative cases that highlight the unique challenges of diagnosis and surgical management of branchial cleft anomalies.